Caracterização química e liberação de nitrogênio de compostos e vermicompostos de casca de arroz e dejetos de animais - Vione, Elaine Luiza Biacchi (2016)
Composting and vermicomposting reduce the volume of wastes and improve their characteristics of use, as fertilizer. However, there is a lack of information about how to use them, depending on the processes and raw materials used. The study performed with the objective of evaluate composts and vermicomposts produced with swine waste, poultry and cattle wastes mixed with rice hulls, regarding the N supply potential in very short cycle crop species. For this, chemical characteristics of composts and vermi-composts were evaluated in relation to fertilizer potential; composts and vermicompost regarding the degree of maturity and phytotoxicity on lettuce (Lactuca sativa L), barley (Hordeum vulgare) and annual ryegrass (Lollium multiflorum) seeds. The contribution in N supply for lettuce plants with and without use of 15N isotopic technique; also the potential for C and N mineralization of composts and vermicomposts in Ultisol for 56 days of incubation in laboratory. The wastes used contributed differences between composts and vermicomposts. Higher content of P, Ca and Mg were obtained in materials produced with poultry waste. The lower C / N ratio indicated that the biological processes influenced the degradation of organic residues and its stabilization. The products obtained with composting and vermicomposting after 60 days of pre-composting were similar, except for the content of K and EC, which were lower in the vermicompost, while lower content of C, cellulose, lignin and greater soluble fraction were found when used cattle waste. In order to cultivate barley and ryegrass, the composts and vermicompost of rice husk with animal wastes presented GI > 50%, considered mature and non-phytotoxic, whereas for lettuce, only cattle vermicompost was considered mature. Among all materials, composts/vermicomposts produced with cattle manure were most mature. The higher N release rates, were found when cattle manure used while lowest when produced with poultry waste. Due to the short cycle of lettuce and also the material stabilization, the contribution of composts/vermicomposts in the N supply was low (about 10%). The N mineralization of materials occurred mainly until the 28th day of incubation and was higher in the composition with cattle and swine manures and lowest in those with poultry waste. In very short cycle species such as lettuce, for adequate N availability, the dose of composts/vermicomposts should be propped according to the mineral N available in the material.